SITE EFFECTS IDENTIFICATION USING HVSR METHOD IN CISARUA HOT SPRING AREA, NATAR, SOUTH LAMPUNG - Farduwin, Alhada; Nugraha, Purwaditya Nugraha; Styawan, Yudha; Lestari, Eka Yunita Purnama; TR, Dina Puspita Julyanti (Engineering Faculty Universitas Lampung, 2025)
Cisarua, which contains a geothermal hot spring, is an intriguing area to investigate due to its location far from any known heat source or volcanic activity. Using the HVSR technique, this study aims to characterize the local site effects based on key parameters: natural frequency (fo), amplification factor (Ao), and average shear-wave velocity down to 30 meters depth (Vs30). Microtremor measurements were conducted at 25 locations across the Cisarua hot spring area, with an average spacing of 300 meters. Each site was recorded for 40–50 minutes, and the data were processed using Geopsy software to extract the HVSR curves, along with the fo and Ao values. The HVSR curves were then inverted using the Particle Swarm Optimization (PSO) algorithm to derive Vs30 values. The results show that fo values range from 0.6 to 1.1 Hz, and Vs30 values are generally below 175 m/s. These two parameters exhibit minimal spatial variation, indicating the presence of thick, soft, and relatively homogeneous sedimentary layers across most of the study area. The Ao values range from 2 to 5, with values below 3 dominating near the geothermal manifestation zone. The spatial distribution of fo and Ao reveals a northwest–southeast trend, which is strongly correlated with the presence of the Lampung–Panjang Fault that likely controls sediment accumulation and layer thickness in the area. Around point T13, Vs30 drops to 125–150 m/s, suggesting localized softening of the soil due to hydrothermal alteration processes. These findings emphasize the interplay between site effects, regional geological structures, and geothermal activity in shaping the dynamic properties of the subsurface in this area.